Development of STEM-Based Project Learning Tools Integrating Local Wisdom of the Gendang Melayu on the Topic of Sound Waves - Musyaddad, Muhammad; Pathoni, Haerul; Alrizal, Alrizal (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2025)
This study aims to assess the feasibility of developing STEM-integrated Project-Based Learning (PjBL) tools incorporating the local wisdom of Gendang Melayu for the topic of sound waves. The development followed the 4D model and was limited to the development stage. In the define phase, several analyses were conducted, including initial-final, learner, task, concept, and learning objectives. The design phase structured the lesson plan (RPP) and student worksheet (LKPD) formats based on PjBL syntax and STEM components. During the development stage, the RPP and LKPD were validated by two expert lecturers and one physics teacher. The RPP scored 94.11% and 91.76%, while the LKPD scored 94% and 95%, all categorized as "very good." A student response questionnaire was also distributed to 23 learners, resulting in an overall average score of 86.6%. These results indicate that the developed tools are valid and practical for use in physics learning. The integration of local cultural elements through the Gendang Melayu project enhances contextual understanding, making physics learning more meaningful and engaging. Thus, the developed learning tools are considered feasible for implementation in sound wave instruction.